The Shadow of the Consumer: Analyzing the Importance of Consumers to the Uptake and Sophistication of Ratings, Certifications, and Eco-Labels. (March 2020) - Bullock, Graham; van der Ven, Hamish
Why has the market uptake and sophistication of information-based environmental governance (IBEG) programs like eco-labeling increased despite mixed signals on the willingness and ability of individual consumers to support such programs? We argue that the extant literature on IBEG focuses too narrowly on individual consumer purchasing decisions to the exclusion of other mechanisms through which consumers, both as individuals and as an imagined collective, exert influence. As a corrective, we present a novel conceptual framework that highlights the different causal mechanisms through which consumers contribute to the uptake and sophistication of IBEG. We call our framework "the shadow of the consumer" since it suggests a more latent and indirect role for consumers than voting-with-one's-wallet. Our analysis adds nuance and complexity to accounts of consumer agency vis-à-vis environmental ratings, standards, certifications, and eco-labels and helps explain the proliferation and growing sophistication of such programs despite the variability of individual consumer support.